Fibroblast Growth Factor 21 Augments Autophagy and Reduces Apoptosis in Damaged Liver to Improve Tissue Regeneration in Zebrafish - Qiang, Weidong; Shen, Tianzhu; Noman, Muhammad; Guo, Jinnan; Jin, Zhongqian; Lin, Danfeng; Pan, Jiaxuan; Lu, Huiqiang; Li, Xiaokun; Gong, Fanghua (Frontiers in Cell and Developmental Biology, 2021)
Regeneration of a part of the diseased liver after surgical resection is mainly achieved by the proliferation of the remaining healthy liver cells. However, in case of extreme loss of liver cells or in the final stages of chronic liver disease, most liver cells are depleted or lose their ability to proliferate. Therefore, to foster liver regeneration, it is of great clinical and scientific significance to improve the survival and proliferation ability of residual hepatocytes. In this study, we conducted experiments on a zebrafish model of targeted ablation of liver cells to clarify the role of fibroblast growth factor 21 (FGF21). We found that FGF21 increased the regeneration area of the damaged liver and improved the survival rate of damaged liver cells by inhibiting cell apoptosis and reducing oxidative stress. Our results also showed that administration of FGF21 upregulated autophagy, and the beneficial effects of FGF21 were reversed by the well-known autophagy inhibitor chloroquine (CQ), indicating that FGF21-activated autophagy played a central role in the treatment. We further showed that the enhancement of autophagy induced by FGF21 was due to the activation of the AMPK-mTOR signaling pathway. Taken together, these data provide new evidence that FGF21 is an effective autophagy regulator that can significantly improve the survival of damaged livers.